The Success of Women's Participation In Resolving Conflicts In Liberia - Dewi Masitoh (Journal of Governance, 2020)
The Civil War that occurred in Liberia has been going on for a long time, where there are two rebel groups, they are: Liberians United for Reconciliation and Democracy (LURD) and Movement for Democracy in Liberia (MODEL). Both of these rebel groups have caused gender inequality in Liberia continuously, especially women who have been victims of this war. However, with the efforts and participation of women from Liberian society, the war was successfully reconciled without creating violence. This research is aimed at realizing that women are not only victims of gender inequality, but can also be 'agents of change' in creating peace and better change for the future of a country. This research will use qualitative research methods, that emphasize the observation and understanding of a social phenomenon, where data is collected through secondary data and literature review. This research will analyze the case using three concepts: Feminism, Gender Equality, and Peace. The research concluded that there have been several efforts that have been made by women to resolve conflicts in Liberia by creating and building peace sustainably so that peace can be stable for a long time. The efforts that have been made by Liberian women are by creating several organizations and affiliations, they are: Woman in the Peacebuilding Network (WIPNET), Mano River Women's Peace Network (MARWOPNET), Association of Female Lawyers of Liberia (AFELL). This long-term peace can improve gender equality in several sectors of Liberian society, such as the economy and political sectors that are getting better and more effective from year to year.